Pyroptosis of MCF7 Cells Induced by the Secreted Factors of hUCMSCs - Yang Jiao; Hongbo Zhao; Guodong Chen; Xiongbo Sang; Luhan Yang; Zongliu Hou; Wei Si; Bingrong Zheng (Hindawi Limited, 2018)
Human umbilical cord mesenchymal stem cells (hUCMSCs) are superior to other sources of mesenchymal stem/stromal cells (MSCs), and they are used as a novel tool for cell-based cancer therapy. However, the mechanism underlying hUCMSC-induced cancer cell death is not clear. In the present study, we aimed to evaluate the effect of secreted factors of hUCMSCs on the breast cancer cell line MCF7 by exposing them to the conditioned medium (CM) of hUCMSCs. We evaluated the morphological changes, cell viability, cell cycle, apoptosis, DNA fragmentation, and interleukin-1β (IL-1β) secretion of CM-exposed MCF7 cells. The results showed that the secreted factors of hUCMSCs could cause MCF7 cell death by inducing pyroptosis. We also sequenced the total RNA, and the differentially expressed genes (DEGs) were subjected to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. A total of 2597 (1822 upregulated and 775 downregulated) genes were identified and 14 pathways were significantly enriched. The results showed that the expression of the pyroptosis-related genes NLRP1 and CASP4 and the inflammation-related pathways changed significantly in MCF7 cells exposed to the CM. To the best of our knowledge, this study is the first to report that the secreted factors of hUCMSCs can cause MCF7 cell pyroptosis. Furthermore, it is the first to examine the global gene expression in MCF7 cells exposed to CM. These results will provide valuable information for further studies on the mechanism of MCF7 cell pyroptosis induced by the secreted factors of hUCMSCs. It will also help understand the effect of hUCMSCs on cell-based breast cancer therapy.